Agents of uncertainty Mysticism, scepticism, Buddhism, art and poetry. - Danvers, John. (Amsterdam : Editions Rodopi, 2012)
Through an analysis of many different examples, Danvers articulates a new way of thinking about mysticism and scepticism, not as opposite poles of the philosophical spectrum, but as two fields of enquiry with overlapping aims and methods. Prompted by a deep sense of wonder at being alive, many mystics and sceptics, like the Buddha, practice disciplines of doubt in order to become free of attachment to fixed appearances, essences and viewpoints, and in doing so they find peace and equanimity. They develop ways of living with impermanence and the unexpected by letting go of adherence to dogmatic
Description based upon print version of record.
Keywords: Buddhism; Mysticism; Scepticism; Mysticism; Skepticism; Buddhism; RELIGION / Mysticism; Electronic books